1999
DOI: 10.1021/jp9926802
|View full text |Cite
|
Sign up to set email alerts
|

Nanosphere Lithography:  Effect of the External Dielectric Medium on the Surface Plasmon Resonance Spectrum of a Periodic Array of Silver Nanoparticles

Abstract: In this paper we examine the effect of solvent on the optical extinction spectrum of periodic arrays of surfaceconfined silver nanoparticles fabricated by nanosphere lithography (NSL). By use of NSL, it is possible to systematically vary the out-of-plane height of the nanoparticles, and by thermal annealing, we can control the nanoparticle shape. We have studied four separate samples of nanoparticle arrays; three samples have nanoparticles that are truncated tetrahedral in shape but that differ in out-of-plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
413
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 529 publications
(445 citation statements)
references
References 26 publications
21
413
0
1
Order By: Relevance
“…31,32 These investigations found that AgNP release is largely due to mechanical stress, but the addition of bleaches can also enhance the release of Ag + into the wash water because of greater oxidation potential. Silver released from textiles during washing will typically be transported to a wastewater treatment plant (WWTP).…”
Section: Release Of Agnps To the Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…31,32 These investigations found that AgNP release is largely due to mechanical stress, but the addition of bleaches can also enhance the release of Ag + into the wash water because of greater oxidation potential. Silver released from textiles during washing will typically be transported to a wastewater treatment plant (WWTP).…”
Section: Release Of Agnps To the Environmentmentioning
confidence: 99%
“…Full-scale and bench-scale studies have shown that silver was removed by about 90% in WWTPs, with a small but significant fraction, partially in the form of AgNPs, remaining in the WWTP effluent while the majority partitioned into the sludge. 31,33,34 Although most of the silver was removed, WWTP effluent still had silver concentrations several orders of magnitude higher than typical river water, and it is expected that AgNPs will be relatively concentrated in WWTP effluents. 29,30,34 The results from these studies also suggest that areas where sludge is land applied will have higher than average concentrations of AgNPs in the soil.…”
Section: Release Of Agnps To the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Posteriormente, vários autores investigaram a influên-cia das condições de preparo destes filmes sobre os espectros SERS. Um substrato SERS foi desenvolvido por van Duyne et al 70,71 e construído por nanolitografia utilizando mascaramento com esferas poliméricas com diâmetro entre 300 e 800 nm. A formação de uma monocamada auto-organizada destas esferas sobre vidro, seguida da deposição de um filme metálico e posterior remoção do material polimérico por dissolução com tolueno, resultou na formação de ilhas metálicas correspondentes ao material que estava nos interstícios das esferas.…”
Section: Substratos Metálicos Sers-ativosunclassified